EFEKTIVITAS PEMBERIAN BEBERAPA BAHAN DAN DOSIS ANESTESI PADA PRAKONDISI KERANG AIR TAWAR (ANODONTA WOODIANA) - Cyska Lumenta (Universitas Padjadjaran, 2012)
The main problem on freshwater mussel culture is the high mortality during implantation process. Freshwater mussel that will be implanted for cultivation need to be conditioned in a state that facilitates the opening of its shell. Because lack of information on the use of anesthesia in the cultivation of freshwater mussel, these principles can be applied is the principle which has been successfully applied in the cultivation of sea mussel. This study aims to determine the best responses to materials anesthetic and dose in precondition of Anodonta woodiana which held in Freshwater Aquaculture Center (BBAT) Tatelu in District Dimembe, Minahasa Regency. The study was designed by using completely randomized design factorial pattern with two factors: materials anesthetic and dose. Material anesthetic factor has 4 degree such as menthol oil, clove oil, nutmeg oiland lemongrass oil. Dose has 3 degree such as 1,5 ml, 2,5 ml and 3,5 ml. Each treatment was repeated 3 times. The results showed that nutmeg oildose of2,5 ml/L more effective for precondition (respons, relaxation time, recovery and mortality rate) than dose of 1,5 ml/l and 3,5 ml/L and than another materials anasthethic (menthol oil, clove oil, and lemongrass oil).